Socio-cultural factors influencing utilization of contraceptives among girls aged 15 to 19 years in Kuria West Subcounty, Migori County - Nyaberi, Jackline; Mogere, Dominic; Mwita, Nancy B. (International Journal Of Community Medicine And Public Health, 2024)
Background: Insufficient contraceptive use among 15–25-year-olds leads to unwanted pregnancies, unsafe abortions, disabilities, infant mortality, and high teen pregnancy rates, with Kenya's high rate of teen pregnancies despite efforts. Methods: Analytical cross-sectional study design was used and 361 teenage girls between 15-19 years in the selected electoral wards at Kuria West Sub County in Migori County, Kenya. Data was collected using administered structured questionnaire, and key informant interview. Quantitative data analysis was conducted using statistical package for the social sciences (SPSS) version 26.0 and involved univariate and bivariate analysis. Bivariate analysis was done through logistic regression was used to test the significance of the association between the dependent and independent variables (p<0.05). Qualitative data was analyzed by thematic content analysis. Results: More than two third 249 (69.0%) of respondents had utilized contraceptives such as condoms (33.3%), injection (25.3%), implants (22.9%), and pills (15.7%). Religious affiliation (ꭓ2=5.576, df=1, p=0.018) was significantly associated with utilization of the contraceptives. Additionally, religion supports the use of contraceptives (ꭓ2=0.061, df=1, p=0.804), culture prohibits the use of contraceptives (ꭓ2=1.496, df=2, p=0.473), discuss contraceptive methods with family (ꭓ2=1.423, df=2, p=0.491), and difficult to engage in sexual discussions with my parents/guardian (ꭓ2=2.707, df=2, p=0.258) had no statistical relationship with utilization of the contraceptives. Conclusions: Central and county government, stakeholders and NGOs should organize health education targeting parents, community and the society which should include, schedules and benefits/importance of utilization of FP services to counter the cultural beliefs.